900MPa-grade ultra-fine grain steel and manufacturing method thereof

By rationally designing chemical composition and optimizing processes in steel, the development of 900MPa grade ultrafine crystal steel has solved the problem that existing steels are difficult to control the yield strength ratio when improving yield strength, and achieved high strength, good low-temperature toughness and elongation. Effect.

CN119433382AActive Publication Date: 2025-02-14BAOSHAN IRON & STEEL CO LTD

Patent Information

Application Number
CN202310946990.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-31
Publication Date
2025-02-14
Estimated Expiration
2043-07-31

AI Technical Summary

Technical Problem

While improving the yield strength, existing steels are difficult to effectively control the yield strength ratio, resulting in an increase in material brittleness, which easily leads to brittle fracture, and conventional fine crystal measures are difficult to significantly improve low-temperature toughness and strength.

Method used

Through the rational design of chemical composition and optimization process, a 900MPa grade ultrafine crystal steel material is developed, which contains specific proportions of C, Si, Mn, Cr, Mo, Ni, Nb, Al and other elements, and is controlled by (Mn+Ni) The ratio of /C and (Cr+Mo)/C is combined with the dynamic recrystallization process to form a biphasic matrix structure of tempered martensite and tempered bainite, and the carbide precipitation is refined.

Benefits of technology

The high strength, good low-temperature toughness and elongation of the steel are achieved, and the risk of brittle fracture is avoided.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119433382A_ABST
    Figure CN119433382A_ABST
Patent Text Reader

Abstract

The invention discloses a 900MPa-grade ultra-fine grain steel material, which contains Fe and inevitable impurities, and further contains the following chemical elements in percentage by mass: 0.20 to 0.28 percent of C, 0.15 to 0.35 percent of Si, 0.90 to 1.40 percent of Mn, 0.80 to 1.30 percent of Cr, 0.30 to 0.65 percent of Mo, 0.86 to 1.25 percent of Ni, 0.01 to 0.08 percent of Nb, 0.015 to 0.05 percent of Al and the balance of Fe and inevitable impurities. In addition, the mass percentage content of each chemical element meets the following conditions: (Mn + Ni) / C is more than or equal to 6 and less than or equal to 12; and 4 < = (Cr + Mo) / C < = 8. Correspondingly, the invention further provides a manufacturing method of the 900 MPa grade ultra-fine grain steel. The yield ratio of the steel is controllable, high strength is guaranteed, and meanwhile good low-temperature toughness and ductility are achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a steel material and a manufacturing method thereof, and in particular to a high-strength steel and a manufacturing method thereof. Background Art

[0002] Yield strength is the basis for judging the plastic deformation of materials, and is usually also the strength design criterion for steel structures. In the usual design and material selection, a higher yield strength is conducive to improving the safety of the system, but too high a yield strength will increase the yield strength ratio of the material, which will increase the brittleness of the material, which is not conducive to the stress release in certain stress concentration areas and is prone to cause brittle fracture.

[0003] Therefore, in the current workpiece processing process, controlling the workpiece to have a suitable yield strength ratio is more beneficial to the service performance of the parts. However, the yield strength ratio should not be too low. During the service process, a too low yield strength ratio can easily cause the workpiece to yield and fail. Therefore, in many engineering applications, many companies hope to control the yield strength ratio of the workpiece steel within the required specific range, so that the steel can obtain higher strength while also having excellent impact toughness.

[0004] In the field of materials, the steel strengthening mechanisms known to those skilled in the art may include: solid solution strengthening, dislocation strengthening, dispersion strengthening, fine grain strengthening and other means. However, in actual preparation, due to the influence of the improvement of the strength grade of steel, the adjustment of the proportion of alloy elements and the diversity of heat treatment processes, the effects of these different strengthening means are difficult to effectively control, which will also lead to a sharp increase in the difficulty of controlling the yield ratio. The grain size of steel produced by conventional fine grain measures is generally not less than 20μm, which has limited effect on improving the low temperature toughness and strength of steel. Summary of the invention

[0005] One of the purposes of the present invention is to provide a 900MPa grade ultrafine grain steel, which obtains a high-strength steel with a fine grain size by rationally designing the chemical composition and combining the optimized process. The yield strength ratio of the high-strength steel is controllable, and while ensuring high strength, it also has good low-temperature toughness and elongation.

[0006] In order to achieve the above object, the present invention provides a 900 MPa grade ultrafine grain steel material, which contains Fe and inevitable impurities, and further contains the following chemical elements in the following mass percentages:

[0007] C: 0.20~0.28%, Si: 0.15~0.35%, Mn: 0.90~1.40%, Cr: 0.80~1.30%, Mo: 0.30~0.65%, Ni: 0.86~1.25%, Nb: 0.01~0.08%, Al: 0.015~0.05%;

[0008] The mass percentage of each chemical element satisfies:

[0009] 6≤(Mn+Ni) / C≤12;

[0010] 4≤(Cr+Mo) / C≤8.

[0011] Furthermore, the present invention also provides a 900MPa grade ultrafine grain steel material, the mass percentage of each chemical element of which is:

[0012] C: 0.20-0.28%, Si: 0.15-0.35%, Mn: 0.90-1.40%, Cr: 0.80-1.30%, Mo: 0.30-0.65%, Ni: 0.86-1.25%, Nb: 0.01-0.08%, Al: 0.015-0.05%; the balance is Fe and unavoidable impurities;

[0013] The mass percentage of each chemical element meets the following requirements:

[0014] 6≤(Mn+Ni) / C≤12;

[0015] 4≤(Cr+Mo) / C≤8.

[0016] In the 900MPa grade ultrafine grain steel of the present invention, the design principles of each chemical element are specifically described as follows:

[0017] C: In the 900MPa ultrafine-grained steel described in the present invention, the C element can effectively improve the hardenability of the steel. The content of the C element in the steel directly determines the phase structure of martensite, which in turn affects the strength of the steel. In addition, the C element can also form carbides with some alloy elements in the steel, and these carbides can produce a dispersion strengthening effect in the matrix. However, it should be noted that the C element content in the steel should not be too high. Too high a C content is very unfavorable for the low-temperature impact toughness of the steel, which will cause the impact toughness of the steel to become lower; at the same time, the C element content in the steel should not be too low. When the C element content in the steel is too low, it will lead to a low content of low-temperature phase transformation structures such as martensite and lower bainite, which makes it impossible for the steel to obtain a higher tensile strength. Based on this, considering the influence of the C element on the performance of the steel, in the 900MPa ultrafine-grained steel described in the present invention, the mass percentage of the C element is controlled between 0.20 and 0.28%.

[0018] Si: In the 900MPa ultrafine-grained steel described in the present invention, the Si element exists in the steel in the form of a substitutional solid solution, which can increase the lattice distortion energy, increase the barrier to dislocation movement, and is beneficial to the improvement of the strength of the steel. At the same time, the Si element can reduce the diffusion capacity of the C element in ferrite. During tempering, an appropriate amount of Si element can avoid the formation of coarse carbides that precipitate at defects. However, the Si content in the steel should not be too high. A higher Si content will have an adverse effect on the welding performance and low-temperature impact toughness of the steel. Therefore, in the 900MPa ultrafine-grained steel described in the present invention, the mass percentage of the Si element is controlled between 0.15 and 0.35%.

[0019] Mn: In the 900MPa ultrafine-grained steel described in the present invention, Mn is a good deoxidizer and desulfurizer. Adding a certain amount of Mn to the steel can produce a good solid solution strengthening effect and improve the strength of the steel. During the quenching process of the steel, Mn will inhibit the diffusion phase transformation, improve the hardenability of the steel, and form a low-temperature phase transformation structure. This type of structure has a higher strength. However, it should be noted that the Mn content in the steel should not be too high. When the Mn element content in the steel is too high, the yield strength of the steel matrix will increase, thereby improving the yield strength ratio of the steel; at the same time, the Mn content in the steel should not be too low. When the Mn element content in the steel is too low, the strength of the steel will be insufficient. Based on this, considering the influence of the Mn element on the performance of the steel, in the 900MPa ultrafine-grained steel described in the present invention, the mass percentage of the Mn element is controlled between 0.90 and 1.40%.

[0020] Cr: In the 900MPa grade ultrafine grain steel described in the present invention, Cr reduces the driving force of the γ-α phase transformation and improves the hardenability. At the same time, Cr is a strong carbide-forming element. After adding an appropriate amount of Cr to the steel, the precipitation of Cr carbides during the tempering process can produce a precipitation strengthening effect, and a high-strength martensitic structure will be formed during the heat treatment process, thereby obtaining a steel with higher strength. At the same time, during the heating process, if the Cr carbides are not completely dissolved, they will be pinned at the grain boundary position, effectively refining the grains. However, it should be noted that the Cr content in the steel should not be too high. When the mass percentage of the Cr element in the steel is too high, coarse carbides will be formed, which will deteriorate the low-temperature impact performance. Therefore, in order to ensure the strength and low-temperature impact performance of the steel, in the 900MPa grade ultrafine grain steel described in the present invention, the mass percentage of the Cr element is controlled between 0.80 and 1.30%.

[0021] Mo: In the 900MPa ultrafine-grained steel described in the present invention, adding an appropriate amount of Mo element can effectively improve the steel's resistance to temper brittleness, inhibit the segregation of harmful elements, and can form fine carbides under a higher temperature tempering environment, thereby improving the strength of the steel. Mo can reduce the carbon activity in the steel, and the carbides are very stable, not easy to grow, and can have the effect of refining the grains. Considering that Mo is a precious alloy element, adding too much Mo element will lead to an increase in cost. Therefore, in the 900MPa ultrafine-grained steel described in the present invention, in order to obtain a match between strength and toughness and welding performance, the mass percentage of Mo element is controlled between 0.30 and 0.65%.

[0022] Ni: In the 900MPa-level ultrafine-grained steel described in the present invention, the Ni element exists in the steel in the form of solid solution. Especially in the component system designed in this case, Ni can effectively reduce the ductile-brittle transition temperature of the material and improve the toughness of the matrix. At the same time, Ni can inhibit the diffusion-type phase transformation and improve the hardenability of the steel. In addition, it should be noted that since Ni is an austenite-forming element, an excessively high content of Ni will lead to an excessively high content of residual austenite in the steel, and the residual austenite will increase the instability of the structure and performance of the steel. Therefore, in the 900MPa-level ultrafine-grained steel described in the present invention, in order to ensure the low-temperature impact toughness and strength of the steel, the mass percentage of Ni is controlled between 0.86 and 1.25%.

[0023] Nb: In the 900MPa ultrafine-grained steel described in the present invention, the Nb element is added to the steel, and it will form high-melting-point carbide and nitride precipitation phases with C and N in the steel, which can inhibit the recrystallization of the steel. These precipitation phases are easy to be segregated at the dislocation line, and have a strong dragging effect on the dislocation movement. However, it should be noted that the Nb content in the steel should not be too high. When the Nb content in the steel is too high, coarse NbC particles will be formed under high-temperature tempering conditions, which will deteriorate the low-temperature impact energy of the steel. Therefore, in the 900MPa ultrafine-grained steel described in the present invention, the mass percentage of the Nb element is controlled between 0.01 and 0.08% to ensure the mechanical properties of the steel.

[0024] Al: In the 900MPa ultrafine-grained steel described in the present invention, Al is a commonly used deoxidizer. Adding an appropriate amount of Al can effectively reduce the oxygen content in the steel. At the same time, Al will form fine AlN precipitation phases during steelmaking, which can effectively pin the grain boundaries during rolling and cooling, inhibit the growth of austenite grains, and achieve the purpose of refining austenite grains and improving the low-temperature toughness of steel. However, it should be noted that the Al content in the steel should not be too high. When the mass percentage of Al in the steel is too high, larger Al-containing oxides will be formed, and coarse Al2O3 hard inclusions will deteriorate the fatigue properties of the steel. Based on this, in order to improve the toughness of the steel, in the 900MPa ultrafine-grained steel described in the present invention, the mass percentage of Al is controlled between 0.015 and 0.05%.

[0025] Moreover, the present invention also designs the synergistic relationship of elements. By controlling the ratio of (Mn+Ni) / C and (Cr+Mo) / C and combining the corresponding heat treatment process according to the ratio of the two, carbon atoms can be precipitated from the interstitial solid solution to form carbides, thereby transforming solid solution strengthening into precipitation strengthening, and realizing multiple coupling of various strengthening mechanisms such as Mn atom solid solution strengthening, C atom solid solution strengthening, carbide precipitation strengthening, and fine grain strengthening, thereby achieving precise control of the yield ratio of steel.

[0026] Furthermore, the 900 MPa grade ultrafine grained steel material of the present invention further contains at least one of the following chemical elements in the following mass percentages:

[0027] 0<Ti≤0.04%;

[0028] 0<Ca≤0.004%;

[0029] 0<Cu≤0.15%.

[0030] In some implementations, in order to obtain a better implementation effect, an appropriate amount of at least one of the elements Ti, Cu and Ca may be further added to the steel.

[0031] Among them, in the 900MPa grade ultrafine-grained steel described in the present invention, the Ti element can form compounds with C and N in the steel, and the formation temperature of TiN is above 1400°C. It is usually precipitated in the liquid phase or δ ferrite, and the dissolution temperature in austenite exceeds 1200°C, which can effectively prevent the growth of austenite grains during the heating process. During the rolling process, the precipitated phase of Ti can serve as a nucleation particle, increase the recrystallization nucleation rate, and prevent grain coarsening, so an appropriate amount of Ti element can be added to the steel.

[0032] However, it should be noted that the Ti content in the steel should not be too high. When the mass percentage of Ti is too high, coarse TiN precipitation will be formed, which will reduce the impact and fatigue properties of the steel. In addition, during the tempering process, too high a Ti content will increase the fluctuation amplitude of the low-temperature impact energy of the steel. In summary, in the 900MPa grade ultrafine-grained steel described in the present invention, an appropriate amount of Ti element can be preferably added, and the mass percentage of Ti element can be controlled to meet 0<Ti<0.04%.

[0033] In addition, an appropriate amount of Cu element can be added to the steel. Cu will form fine nano-scale ε-Cu precipitation during the tempering process, thereby improving the strength of the steel. At the same time, adding a certain amount of Cu element is also beneficial to improving the corrosion resistance of the steel. However, considering that the melting point of Cu is relatively low, if the mass percentage of Cu added is too high, Cu will be enriched at the grain boundary during the heating austenitization process, resulting in weakening of the grain boundary and cracking. Based on the above considerations, in the 900MPa grade ultrafine grain steel described in the present invention, an appropriate amount of Cu element can be preferably added, and the amount of Cu added is controlled to be 0<Cu≤0.15%.

[0034] In addition, an appropriate amount of Ca element can be added to the 900MPa grade ultrafine grain steel of the present invention, and the amount of Ca added is controlled to be 0<Ca≤0.004%. Ca element can cooperate with S element in steel to form CaS, which can improve the size and morphology of inclusions and increase the fatigue life of steel.

[0035] Furthermore, in the 900 MPa grade ultrafine grain steel material of the present invention, the mass percentage of each element also satisfies: 0.2≤(Nb+2Ti) / (C+N)≤0.6.

[0036] In some embodiments of the present invention, while controlling the mass percentage of a single chemical element, the synergistic relationship between the elements is controlled to satisfy the above formula, which can further improve the performance of the steel.

[0037] Furthermore, among the inevitable impurities in the 900 MPa grade ultrafine grained steel material of the present invention, the content of each impurity element satisfies at least one of the following conditions:

[0038] P≤0.015%;

[0039] S≤0.003%;

[0040] N≤0.015%;

[0041] O≤0.0025%.

[0042] In the 900MPa grade ultrafine grain steel of the present invention, P, S, N, and O are all impurities in the steel. Under the condition that the technical conditions permit, the lower the content of P, S, N, and O in the steel, the better.

[0043] P: P in steel will segregate at the grain boundary, which will reduce the binding energy of the grain boundary, thereby deteriorating the low-temperature impact performance of the steel. In addition, the coexistence of P and Mn will aggravate the temper brittleness of the steel. In order to reduce the intergranular fracture caused by the grain boundary segregation of P, reduce the energy absorbed by the steel when it is impacted, and ensure the low-temperature impact toughness of the round steel, in some embodiments, the mass percentage of P can be controlled to meet: P≤0.015%.

[0044] S: The solubility of S element in delta ferrite and austenite is very low. During the solidification of molten steel, S will form a large number of sulfide inclusions with Fe and Mn in the steel. Among them, FeS will become liquid at 989°C, causing hot brittle cracking of the steel during rolling; and MnS has excellent plasticity. After rolling, it will become long strips and distribute at the grain boundary, "cutting" the continuity of the steel matrix, which will have an adverse effect on the fatigue life and impact toughness of the material. Therefore, in order to ensure that the steel has good low-temperature impact performance and fatigue life, in some embodiments, the mass percentage of S can be controlled to meet: S≤0.003%.

[0045] N: The N element can form AlN or TiN in the steel and play a role in refining the austenite grains. However, it should be noted that the increase in the mass percentage of N will lead to an increase in its enrichment at the defects and the formation of coarse nitride precipitation particles, which will affect the low-temperature impact energy of the steel. Based on this, in some embodiments, the mass percentage of N can be controlled to meet: N≤0.0150%.

[0046] O: O element can form compounds such as Al2O3 and TiO with Al and Ti elements in steel, which are not conducive to the performance of steel. In order to ensure the uniformity of steel structure and low-temperature impact toughness, in some embodiments, the mass percentage of O can be controlled to meet: O≤0.0025%.

[0047] Furthermore, in the 900 MPa grade ultrafine grain steel described in the present invention, its microstructure matrix is ​​tempered martensite + tempered bainite.

[0048] Furthermore, in the 900 MPa grade ultrafine grain steel material of the present invention, the average grain size of the tempered martensite and the tempered bainite does not exceed 10 μm.

[0049] Furthermore, the 900MPa-grade ultrafine-grained steel described in the present invention has a yield strength ≥800MPa, a tensile strength Rm ≥900MPa, a yield strength ratio of 0.85 to 0.95, an elongation A ≥15%, a cross-sectional shrinkage ≥50%, and a Charpy impact energy Akv ≥110J at -20°C.

[0050] Correspondingly, another object of the present invention is to provide a method for manufacturing 900MPa grade ultrafine-grained steel, which has a simple process flow and is easy to control. At the same time, the round steel obtained by combining with a reasonable chemical composition ratio has good low-temperature toughness and elongation while ensuring high strength.

[0051] In order to achieve the above object, the present invention also proposes a method for manufacturing a 900 MPa grade ultrafine grain steel as described above, which comprises the steps of:

[0052] (1) Smelting and casting;

[0053] (2) Heating, forging or rolling: wherein the starting rolling or forging temperature is controlled to be 980-1050°C, the final rolling or forging temperature is ≥850°C, and the deformation amount per single pass is controlled to be 30-60%;

[0054] (3) Quenching: The steel is heated to an austenitizing temperature of 860-960°C, followed by water quenching;

[0055] (4) Tempering: The tempering temperature is 580-640°C, and air cooling or water cooling is performed after tempering.

[0056] In the manufacturing method described in the present invention, the deformation amount and rolling temperature of a single rolling pass are controlled to control the number of particles of the carbide precipitation phase, thereby realizing dynamic recrystallization process control of the steel matrix structure, and realizing ultrafine grain control of the steel matrix, making the matrix structure uniform and fine, and ensuring the size of the martensite laths after quenching of the steel. It is further combined with the tempering process to realize controllable diffusion distance of carbon atoms within a certain range, thereby making the spacing between carbides more uniform and fine, so that the carbides have a better effect of hindering dislocations when the material yields and deforms.

[0057] Among them, under the condition of controlling the final rolling or final forging temperature ≥850℃, the steel can undergo recrystallization and strain-induced precipitation, thereby forming a refined bainite and martensite multiphase matrix structure with fine carbonitride precipitation, thereby further improving the performance of the steel.

[0058] In the manufacturing method described in the present invention, the inventors have also optimized the design of the quenching and tempering heat treatment process. The austenitizing temperature is controlled between 860 and 960°C in the quenching step because: in this catalytic process, the carbonitrides of Nb, Ti, Cr and Mo in the steel can be fully or partially dissolved, and the undissolved carbonitrides can effectively pin the austenite grain boundaries, avoiding the austenite grains from being too coarse, achieving the purpose of grain refinement after quenching, and improving the strength and toughness of the steel.

[0059] Accordingly, a water quenching process is used for cooling after austenitization. During the cooling process, the alloy elements dissolved in austenite can effectively improve the hardenability of the steel, which can make the final martensite finer, so that the final round steel has high strength and good toughness.

[0060] In addition, the tempering heat treatment of round steel is controlled at a tempering temperature between 580 and 640°C after quenching because: during the quenching process, the steel matrix forms lower bainite and martensite structures with large defect density, with large internal distortion energy, and some areas will produce stress concentration and uneven internal stress distribution. During the high-temperature tempering process, Nb will form fine and dispersed carbonitrides with C and N, and Cr and Mo will also form fine carbides to precipitate, achieving a dispersion strengthening effect; at the same time, due to the annihilation of high-density dislocations and the movement of small-angle grain boundaries, it will make the microstructure of the steel more uniform, thereby improving the phenomenon of low elongation after tempering.

[0061] Within the tempering temperature range defined in the present invention, the steel can be guaranteed to have good toughness and plasticity, effectively reducing the internal stress of the steel, which is beneficial to the processing and use of the steel, such as the production of high-performance R4 offshore platform mooring chains and engineering structure steel.

[0062] In addition, it should be noted that in step (1), the steel can be smelted in a converter or an electric furnace and cast into a continuous casting billet. Specifically, the casting process can be die casting or continuous casting.

[0063] Furthermore, in some embodiments of the manufacturing method described in the present invention, in step (2), the ingot is heated and then rolled or forged once to directly roll or forge the ingot to the size of the final product, wherein the heating temperature of the ingot is 1100-1200°C.

[0064] Furthermore, in some other embodiments of the manufacturing method described in the present invention, in step (2), the ingot is first heated and the intermediate billet is rolled, the ingot is rolled into an intermediate billet, and then the intermediate billet is heated, and final rolled or final forged to obtain the final product size, wherein the ingot heating temperature is 1100-1200°C; the intermediate billet heating temperature is 1100-1200°C.

[0065] In some embodiments, the heating temperature is controlled between 1100 and 1200°C because: the heating process carried out at this heating temperature can partially or completely dissolve the carbonitrides of Nb, V and Ti, and the carbides of Cr and Mo in austenite; in the subsequent rolling or forging and quenching process, Nb, V and Ti form fine carbonitrides, which can pin the austenite grain boundary, increase the nucleation rate, and facilitate dynamic recrystallization nucleation during rolling, and refine the rolled structure of the steel. In addition, Cr and Mo dissolved in austenite can also improve the hardenability and hardenability of the steel.

[0066] The 900MPa grade ultrafine grain steel and the manufacturing method thereof of the present invention have the following advantages and beneficial effects:

[0067] The present invention is significantly different from the existing 900MPa grade steel. The current 900MPa grade ultrafine grain steel mainly adopts the low carbon + high manganese technology route, and the carbon content is generally below 0.20%. The technology route adopted by the present invention is significantly different from the existing solution component system, and the present invention can also achieve precise control of the yield strength ratio within a certain range.

[0068] The present invention innovatively adopts the control of the ratio of (Mn+Ni) / C and (Mo+Cr) / C and the dynamic recrystallization process during rolling, thereby realizing the coupling of solid solution strengthening, precipitation strengthening and fine grain strengthening of steel, and achieving precise control of the high strength and toughness and yield strength ratio of the material.

[0069] The 900MPa-level ultrafine-grained steel of the present invention can form a dual-phase matrix structure of tempered martensite and tempered bainite, and refined carbides are precipitated on the matrix, thereby eliminating the internal stress of the steel and having good structural uniformity.

[0070] In addition, the 900 MPa grade ultrafine grain steel described in the present invention has a wide process window and can be commercially produced in batches on a bar or plate production line. In some embodiments, it can manufacture round steel with a diameter of 30 to 180 mm.

[0071] In some embodiments, the yield strength Rp of the 900 MPa grade ultrafine grain steel of the present invention is 0.2 ≥800MPa, tensile strength R m ≥900MPa, yield strength ratio Rp 0.2 / R m It is 0.85~0.95, the elongation A≥15%, the cross-sectional shrinkage Z≥50%, and the Charpy impact energy Akv below -20℃≥110J.

[0072] The 900MPa grade ultrafine grain steel of the present invention can be effectively applied to the occasions requiring high strength and toughness materials, such as marine engineering mooring chains, automobiles, mechanical engineering structures and other fields, and has wide applicability, good use prospects and value. BRIEF DESCRIPTION OF THE DRAWINGS

[0073] Figure 1 The 500-fold metallographic structure photograph of Example 3 of the present invention under a microscope is shown. DETAILED DESCRIPTION

[0074] The 900 MPa grade ultrafine grain steel and the manufacturing method thereof described in the present invention will be further explained and illustrated below in conjunction with the accompanying drawings and specific embodiments of the specification. However, such explanation and illustration do not constitute an improper limitation on the technical solution of the present invention.

[0075] The 900 MPa grade ultrafine grain steel materials of Examples 1-8 and Comparative Examples 1-6 were prepared by the following steps:

[0076] 1) Smelting: The molten steel is smelted in an electric furnace or a converter according to the composition ratios shown in Table 1-1 and Table 1-2.

[0077] 2) Casting: The molten steel obtained from smelting is cast into ingots by mold casting or continuous casting.

[0078] 3) Heating; forging or rolling: The ingot is heated and then forged or rolled to obtain a steel billet. The starting rolling or forging temperature is controlled to be 980-1050°C, the final rolling or forging temperature is ≥850°C, and the deformation amount per single pass is controlled to be 30-60%.

[0079] Among them, Examples 5-8 and Comparative Examples 1 and 5 only undergo one heating and one rolling or forging to directly roll or forge the ingot to the final size of the finished product.

[0080] The ingots of Examples 1-4, Comparative Examples 2-4 and Comparative Example 6 are first rolled to a specified intermediate billet size, and then the intermediate billet is heated and finished rolled or forged to roll the intermediate billet to the size of the final finished product, wherein the heating temperature of the ingot is 1100-1200°C and the heating temperature of the intermediate billet is 1100-1200°C.

[0081] 4) Quenching: The steel billet is heated to an austenitizing temperature of 860-960°C, and water quenching is performed after austenitizing.

[0082] 5) Tempering: The tempering temperature is 580-640℃, and air cooling or water cooling is performed after tempering.

[0083] Table 1-1 lists the mass percentage ratios of the chemical elements of the 900 MPa grade ultrafine grain steels of Examples 1-8 and the comparative round steels of Comparative Examples 1-6.

[0084] Table 1-1 (wt.%, the balance is Fe and other unavoidable impurities except P, S, N and O)

[0085]

[0086]

[0087] Table 1-2 lists the synergistic relationship of the chemical elements of the 900 MPa grade ultrafine grain steels of Examples 1-8 and the comparative round steels of Comparative Examples 1-6.

[0088] Table 1-2.

[0089] serial number 6≤(Mn+Ni) / C≤12 4≤(Cr+Mo) / C≤8 0.2≤(Nb+2Ti) / (C+N)≤0.6 Example 1 9.38 5.68 0.30 Example 2 9.31 6.94 0.32 Example 3 9.45 5.75 0.24 Example 4 9.16 7.31 0.21 Example 5 10.24 7.66 0.22 Example 6 7.91 4.18 0.50 Example 7 7.36 6.19 0.44 Example 8 7.71 5.96 0.24 Comparative Example 1 10.20 7.09 0.36 Comparative Example 2 15.28 9.28 0.20 Comparative Example 3 9.26 7.11 0.14 Comparative Example 4 10.20 7.09 0.36 Comparative Example 5 9.22 9.51 0.22 Comparative Example 6 10.20 7.09 0.36

[0090] Note: In Table 1-2, the elements in “(Mn+Ni) / C”, “(Cr+Mo) / C” and “(Nb+2Ti) / (C+N)” are substituted with the mass percentage of the corresponding chemical elements; the results of the above formulas are rounded to two decimal places.

[0091] Table 2 lists the specific process parameters of the 900 MPa grade ultrafine grain steels of Examples 1-8 and the comparative round steels of Comparative Examples 1-6 in the above process steps.

[0092] Table 2

[0093]

[0094] The present invention also samples the 900 MPa grade ultrafine grain steel materials of Examples 1-8 and Comparative Examples 1-6 to observe their microstructures using a metallographic microscope, and the observation results are listed in Table 3.

[0095] Table 3.

[0096]

[0097]

[0098] It can be seen from Table 3 that the microstructure matrix of each embodiment of the present invention is tempered martensite + tempered bainite, and has ultrafine grains, and the average grain size is ≤8.5 μm.

[0099] also, Figure 1 The 500-fold metallographic structure photograph of the 900 MPa grade ultrafine-grained steel of Example 3 under an optical microscope is shown.

[0100] from Figure 1 It can be seen that the microstructure matrix of the steel is a complex phase structure of tempered martensite + tempered bainite.

[0101] In order to verify the implementation effects of the embodiments of the present invention, samples of 900 MPa grade ultrafine grain steels of embodiments 1-8 and comparative examples 1-6 were taken for mechanical property tests, and the test results are listed in Table 4. The relevant test process is as follows:

[0102] Tensile test: At room temperature, according to GB / T 228-2010 "Room temperature test method for tensile test of metallic materials", the yield strength Rp of the round steel samples of each embodiment and comparative example at room temperature was measured. 0.2 , tensile strength R m , elongation A and section shrinkage Z.

[0103] Impact test: at -20°C, in accordance with GB / T 229-2020 “Charpy Pendulum Impact Test Method for Metallic Materials”, the Charpy impact energy Akv of the round steel samples of each embodiment and comparative example at -20°C was measured.

[0104] Table 4.

[0105]

[0106]

[0107] Note: The longitudinal impact energy Akv at -20℃ in Table 4 records the values ​​of three sets of parallel tests.

[0108] It can be seen from Table 4 that the yield strength of the steels of Examples 1 to 8 of the present invention is greater than 826 MPa, the tensile strength is greater than 911 MPa, the yield strength ratio is 0.88 to 0.92, the Charpy impact energy Akv at -20°C is greater than 120 J, the elongation is ≥17%, and the cross-sectional shrinkage is ≥67%. This fully demonstrates that the 900 MPa-grade ultrafine-grained steel of the present invention has a controllable yield strength ratio, and has good low-temperature toughness and elongation while ensuring high strength.

[0109] It should be noted that the combination of the various technical features in this case is not limited to the combination described in the claims of this case or the combination described in the specific embodiments. All technical features recorded in this case can be freely combined or combined in any way unless there is a contradiction between them.

[0110] It should also be noted that the above-listed embodiments are only specific embodiments of the present invention. Obviously, the present invention is not limited to the above embodiments, and similar changes or modifications made therewith can be directly derived or easily associated with the contents disclosed by those skilled in the art from the present invention, and all should belong to the protection scope of the present invention.

Claims

1. A 900 MPa grade ultrafine grain steel material containing Fe and unavoidable impurities, characterized in that: It also contains the following chemical elements in the following mass percentages: C: 0.20~0.28%, Si: 0.15~0.35%, Mn: 0.90~1.40%, Cr: 0.80~1.30%, Mo: 0.30~0.65%, Ni: 0.86~1.25%, Nb: 0.01~0.08%, Al: 0.015~0.05%; The mass percentage of each chemical element satisfies: 6≤(Mn+Ni) / C≤12; 4≤(Cr+Mo) / C≤8.

2. The 900 MPa grade ultrafine grain steel material according to claim 1, characterized in that: The mass percentage of each chemical element is: C: 0.20-0.28%, Si: 0.15-0.35%, Mn: 0.90-1.40%, Cr: 0.80-1.30%, Mo: 0.30-0.65%, Ni: 0.86-1.25%, Nb: 0.01-0.08%, Al: 0.015-0.05%; the balance is Fe and other inevitable impurities; The mass percentage of each chemical element satisfies: 6≤(Mn+Ni) / C≤12; 4≤(Cr+Mo) / C≤8.

3. The 900 MPa grade ultrafine grain steel material according to claim 1 or 2, characterized in that: It also contains at least one of the following chemical elements in the following mass percentages: 0<Ti≤0.04%; 0<Ca≤0.004%; 0<Cu≤0.15%.

4. The 900 MPa grade ultrafine grain steel material according to claim 1 or 2, characterized in that: The mass percentage of each element also satisfies: 0.2≤(Nb+2Ti) / (C+N)≤0.

6.

5. The 900 MPa grade ultrafine grain steel material according to claim 1 or 2, characterized in that: Among other inevitable impurities, the content of each impurity element satisfies at least one of the following conditions: P≤0.015%, S≤0.003%, N≤0.015%, O≤0.0025%.

6. The 900 MPa grade ultrafine grain steel material according to claim 1 or 2, characterized in that: Its microstructure matrix is ​​tempered martensite + tempered bainite.

7. The 900 MPa grade ultrafine grain steel material according to claim 6, characterized in that: The average grain size of tempered martensite and tempered bainite does not exceed 10 μm.

8. The 900 MPa grade ultrafine grain steel material according to claim 1 or 2, characterized in that: Its yield strength is ≥800MPa, tensile strength Rm is ≥900MPa, yield strength ratio is 0.85-0.95, elongation A is ≥15%, cross-sectional shrinkage is ≥50%, and Charpy impact energy Akv at -20℃ is ≥110J.

9. The method for manufacturing a 900 MPa grade ultrafine grain steel material according to any one of claims 1 to 8, characterized in that: It includes the steps of: (1) Smelting and casting; (2) Heating, forging or rolling, wherein the starting rolling or forging temperature is controlled to be 980-1050°C, the final rolling or forging temperature is ≥850°C, and the deformation amount per single pass is controlled to be 30-60%; (3) Quenching: The steel is heated to an austenitizing temperature of 860-960°C, followed by water quenching; (4) Tempering: The tempering temperature is 580-640℃.

10. The manufacturing method according to claim 9, characterized in that: In step (2), the ingot is heated and then rolled or forged once to directly roll or forge the ingot to the size of the final product, wherein the heating temperature of the ingot is 1100-1200°C.

11. The manufacturing method according to claim 9, characterized in that: In step (2), the ingot is first heated and the intermediate billet is rolled, the ingot is rolled into an intermediate billet, and then the intermediate billet is heated, and final rolled or final forged to obtain the final product size, wherein the heating temperature of the ingot is 1100-1200°C; the heating temperature of the intermediate billet is 1100-1200°C.

Citation Information

Patent Citations

  • Ultrahigh-strength low-temperature-toughness steel, ultrahigh-strength low-temperature-toughness bar and manufacturing method of ultrahigh-strength low-temperature-toughness bar

    CN112011727A

  • Hot-rolled hot-formed steel for 2000MPa-grade ultrahigh-toughness spoke and preparation method of hot-rolled hot-formed steel

    CN114107636A

  • Low-temperature-resistant anchor chain

    CN114369759A

  • High-strength steel with excellent weather resistance and manufacturing method thereof

    CN114592153A

Cited By

  • Engineering structure steel with ultralow magnetic conductivity in low-temperature environment and manufacturing method thereof

    CN120719223A